2014
DOI: 10.1037/a0036023
|View full text |Cite
|
Sign up to set email alerts
|

Reaching new heights: Comparing interpretation bias modification to exposure therapy for extreme height fear.

Abstract: Objective Cognitive models of anxiety disorders posit that biases in interpretation maintain, and potentially cause, anxiety. This study tested whether it is possible to decrease height fear symptoms through cognitive bias modification for interpretations (CBM-I). Additionally, the clinical utility of CBM-I was tested by comparing it to an already established treatment: exposure therapy. Method Extremely height fearful (N = 110) individuals participated in the study. Acrophobic symptoms were measured before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Following other studies from our lab (e.g., Steinman & Teachman, 2014), we used multiple iterations of the training set to reinforce the modification of interpretation bias. After completing the first round as described above, participants were then instructed to read each scenario and comprehension question out loud (similar to Steinman & Teachman, 2014). The third time, participants saw the same scenarios but with a blank space in place of the final word fragment.…”
Section: Development Of Training Stimulimentioning
confidence: 99%
“…Following other studies from our lab (e.g., Steinman & Teachman, 2014), we used multiple iterations of the training set to reinforce the modification of interpretation bias. After completing the first round as described above, participants were then instructed to read each scenario and comprehension question out loud (similar to Steinman & Teachman, 2014). The third time, participants saw the same scenarios but with a blank space in place of the final word fragment.…”
Section: Development Of Training Stimulimentioning
confidence: 99%
“…The adult anxiety literature has shown that directly reducing negative cognitive biases through CBM-I can lead to reductions in anxiety symptoms, highlighting a causal role for cognitive biases in anxiety and, in turn, the clinical utility of CBM-I (MacLeod & Mathews, 2012; Steinman & Teachman, 2014). Thus, several child and adolescent studies have adapted the ambiguous scenario paradigm that has commonly been used in adult CBM-I studies.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive bias modification for threat interpretation (CBM-I) refers to computerized training in interpreting ambiguity in a benign way, so as to reduce threat-related interpretations and increase benign interpretations of ambiguous situations in participants' everyday life (Mathews & Mackintosh, 2000). The adult anxiety literature has shown that directly reducing negative cognitive biases through CBM-I can lead to reductions in anxiety symptoms, highlighting a causal role for cognitive biases in anxiety and, in turn, the clinical utility of CBM-I (MacLeod & Mathews, 2012;Steinman & Teachman, 2014). Thus, several child and adolescent studies have adapted the ambiguous scenario paradigm that has commonly been used in adult CBM-I studies.…”
Section: Cognitive Bias Modification For Interpretationmentioning
confidence: 99%